2019
DOI: 10.21203/rs.2.14280/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intimate partner violence against pregnant women in East Gojjam Zone, Ethiopia

Abstract: Background: Though underestimated, intimate partner violence (IPV) against women in Ethiopia is among the highest in the world. The overall aim of the study was to assess the prevalence and forms of intimate partner violence during pregnancy, associated factors, and recommendations to reduce the act. Methods: A cross-sectional study was conducted from January 25 to February 15, 2018 in government health facilities, North West Ethiopia. Married women who seek antenatal care service were participated in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In current study among women with history of IPV, Psychological/emotional violence was the common type of violence 39.9%( 95% CI: 35.5-44.7).This nding is consistent with Gambia 43% [13], East gojjam Zone 44.2%) [10] but higher than Kisumu District Hospital in Kenya 29% [25], Public Health Facilities of Hossana Town 20% [23],O a District in Tigray 25.1%) [26] and Debre Markos town health 29.1% [11]. The probable justi cation for such discrepancy may be observed due to lack of awareness, low level of education, society perception on IPV in our study area.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In current study among women with history of IPV, Psychological/emotional violence was the common type of violence 39.9%( 95% CI: 35.5-44.7).This nding is consistent with Gambia 43% [13], East gojjam Zone 44.2%) [10] but higher than Kisumu District Hospital in Kenya 29% [25], Public Health Facilities of Hossana Town 20% [23],O a District in Tigray 25.1%) [26] and Debre Markos town health 29.1% [11]. The probable justi cation for such discrepancy may be observed due to lack of awareness, low level of education, society perception on IPV in our study area.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the overall prevalence of IPV among pregnant women found to be 40.8%.This nding is lower as compared to studies Northern Cyprus 68% [12],Gambia 62% [13], Abuja Teaching Hospital in Nigeria 56.3% [14], Oyo state in Nigeria 72.0% [15], Maputo city of Mozambique was 70.2%[16], Uganda 56% [5], West Pokot county of Kenya 66.9% [17], East Gojjam zone 46.4% [10] and Bale zone 59.0%…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In 2014, a cross sectional study in Hossana, reported IPV during pregnancy of 23% [9]while in the same year a cross sectional study in west Shewa, Oromia found IPV during pregnancy to be 64% [8]. Another cross sectional study in 2018 in Debre Markos, Amhara region reported prevalence of 41.1% [7] and in the same year almost similar nding(46.4%) was reported from cross sectional study in east gojjam [10]. The aim of this study was to assess the magnitude and factors associated with IPV among pregnant women attending ANC at SPHMMC and a liate hospitals.…”
Section: Introductionmentioning
confidence: 67%